Abnormal Internal Friction Peaks in Single-Crystal Ice. - Stallman,P E; Itagaki,K (1977)
A series of sharp skewed internal friction peaks were observed during warming of single-crystal ice after cooling below -120 C (153 K), the cubic-hexagonal transition temperature. The peaks were higher when the strain amplitude was lower. Since handling and annealing strongly affect the occurrence of the skewed peaks, those peaks are probably related to the stacking fault process in hexagonal-cubic transition. (Author)